Double positivity for HPV-DNA/p16ink4a is the biomarker with strongest diagnostic accuracy and prognostic value for human papillomavirus related oropharyngeal cancer patients. (March 2018) - Mena, Marisa; Taberna, Miren; Tous, Sara; Marquez, Sandra; Clavero, Omar; Quiros, Beatriz; Lloveras, Belen; Alejo, Maria; Leon, Xavier; Quer, Miquel; Bagué, Silvia; Mesia, Ricard; et al.
Highlights: Six biomarkers of HPV-relatedness were assessed in 788 oropharyngeal cancers. A low HPV attributable fraction in oropharyngeal cancer was observed. Double positivity for HPV-DNA/p16 INK4a showed strongest prognostic value. Abstract: Background: The etiologic role of human papillomaviruses (HPV) in oropharyngeal cancer (OPC) is well established. Nevertheless, information on survival differences by anatomic sub-site or treatment remains scarce, and it is still unclear the HPV-relatedness definition with best diagnostic accuracy and prognostic value. Methods: We conducted a retrospective cohort study of all patients diagnosed with a primary OPC in four Catalonian hospitals from 1990 to 2013. Formalin-fixed, paraffin-embedded cancer tissues were subjected to histopathological evaluation, DNA quality control, HPV-DNA detection, and p16 INK4a /pRb/p53/Cyclin-D1 immunohistochemistry. HPV-DNA positive and a random sample of HPV-DNA negative cases were subjected to HPV- E6*I mRNA detection. Demographic, tobacco/alcohol use, clinical and follow-up data were collected. Multivariate models were used to evaluate factors associated with HPV positivity as defined by four different HPV-relatedness definitions. Proportional-hazards models were used to compare the risk of death and recurrence among HPV-related and non-related OPC. Results: 788 patients yielded a valid HPV-DNA result. The percentage of positive cases was 10.9%, 10.2%, 8.5% and 7.4% for p16 INK4a, HPV-DNA, HPV-DNA/HPV- E6*I mRNA, and HPV-DNA/p16 INK4a, respectively. Being non-smoker or non-drinker was consistently associated across HPV-relatedness definitions with HPV positivity. A suggestion of survival differences between anatomic sub-sites and treatments was observed. Double positivity for HPV-DNA/p16 INK4a showed strongest diagnostic accuracy and prognostic value. Conclusions: Double positivity for HPV-DNA/p16 INK4a, a test that can be easily implemented in the clinical practice, has optimal diagnostic accuracy and prognostic value. Our results have strong clinical implications for patients' classification and handling and also suggest that not all the HPV-related OPC behave similarly.